Consistency checking and combining measurement results for a wireless sensor network - Duta, M; Henry, M (2008)
Two similar approaches are presented for performing consistency checking of measured data in cases where associated uncertainty values are provided. The key differences between the approaches concern the determination of a consistent subset, and the treatment of measured data deemed to fall outside that subset. The different approaches reflect the priorities of their respective domains of application, namely on-line sensor monitoring, and interlaboratory comparisons.